Association of mean platelet volume with angiographic thrombus burden and short‐term mortality in patients with ST‐segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. Issue 1 (23rd February 2015) - Lai, Hong‐Mei; Xu, Rui; Yang, Yi‐Ning; Ma, Yi‐Tong; Li, Xiao‐Mei; Zhao, Qian; Chen, Qing‐Jie; Zhai, Hui; Liu, Fen; Chen, Bang‐Dang
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to evaluate the impact of mean platelet volume (MPV) on the intracoronary thrombus burden and short‐term mortality in patients with ST‐segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Background Platelets play a crucial role in the pathophysiology of coronary artery disease. MPV has been reported to be an indicator of platelet reactivity. Methods A total of 649 consecutive STEMI patients who underwent primary PCI between January 2008 and December 2013 were enrolled and divided into two groups based on the thrombus burden: the large thrombus burden (LTB) group and the small thrombus burden (STB) group. The primary endpoint was all‐cause mortality at 30 days. Result The LTB group had significantly higher admission MPV compared with the STB group (10.77 ± 1.22 vs. 9.95 ± 1.03, P < 0.001). The cumulative 30‐day all‐cause mortality rate was significantly higher in the groups with high MPV and LTB (9.8% vs. 2.5%, P < 0.001, 8.6% vs. 4.1%, P = 0.036, respectively). In a receiver operating characteristics analysis, MPV ≥ 10.2 predicted LTB with 73.5% sensitivity and 68.9% specificity. Multivariate logistic regression analysis demonstrated MPV was an independent predictor of large intracoronary thrombus burden (OR 1.794, 95% CI 1.533 to 2.100, P < 0.001) and 30‐day all‐cause mortality (HR 1.408, 95% CI 1.040 to 1.906, P = 0.027). Conclusions Increased MPV at admission is an independent predictor of large intracoronary thrombus burden and short‐term mortality. It may be a useful biomarker for risk stratification in patients with STEMI undergoing primary PCI. © 2015 Wiley Periodicals, Inc.